New species of the leafhopper genera Kusala Dworakowska and Diomma Motschulsky (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) with description of a new subgenus - Cao, Yanghui; Dmitriev, Dmitry A.; Zhang, Yalin (Zootaxa, 2018)
Generic characteristics of the leafhopper genus Kusala Dworakowska are revised, and a new subgenus Scodela is established. A species checklist of the Kusala is provided and three new species are added: Kusala (Kusala) viraktamathi, K. (Scodela) directa and K. (S.) sinuata spp. nov.. The related genus Diomma Motschulsky is also redescribed and a new species is described: Diomma (Diomma) sangzhiensis sp. nov..